UTILISATION AND DISTRIBUTION OF MEMBERS OF MENTHINAE (LAMIACEAE) IN THREE DISTRICTS OF JAMMU PROVINCE (J&K) - NISHA BHAGAT,; GEETA SHARMA, (International Journal of Pharma and Bio Sciences, 2017)
Jammu province of J&K state exhibits marked altitudinal, climatic and ecological variations. This variability is responsible for the rich biodiversity in the region which supports many aromatic species of subtribe Menthinae (tribe Mentheae: subfamily Nepetoideae: family Lamiaceae) viz. Mentha arvensis, Mentha longifolia, Mentha spicata, Mentha piperita, Origanum vulgare, Thymus serpyllum and Micromeria biflora. Of these, M. spicata and M. piperita are the cultivated forms, whereas the rest are wild types. Regarding the distribution of members of Menthinae in Jammu, Udhampur and Kathua districts of Jammu Province, fragmentary information is on the record. In order to locate present taxa in these less explored areas, surveys were conducted during 2016-17 and data were gathered. Besides, information regarding their utilisation was obtained from the local inhabitants. Present communication entailing data on distribution and utility of seven aromatic taxa is likely to instigate local people for cultivating theseon large scale for commercial purpose.